2016
DOI: 10.4081/ejh.2016.2590
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of heparanase isoforms and syndecan-1 proteins in colorectal adenomas

Abstract: The proteoglycan syndecan-1 and the endoglucuronidases heparanase-1 and heparanase-2 are involved in molecular pathways that deregulate cell adhesion during carcinogenesis. Few studies have examined the expression of syndecan-1, heparanase-1 and mainly heparanase-2 proteins in non-neoplastic and neoplastic human colorectal adenoma tissues. The aim of this study was to analyze the correlation among the heparanase isoforms and the syndecan-1 proteins through immunohistochemical expression in the tissue of colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…The present investigation results indicated that HS proteoglycan SYND1 has higher protein and mRNA expression in tumor tissues than non-neoplastic tissues. Such a result was also observed in our group's previous study, which found a significant decrease in CRC tissue's SYND1 protein level than the non-neoplastic colorectal tissue [37]. It is important to note that such studies compared samples from tumor tissues and tissues of patients not affected by neoplasia.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The present investigation results indicated that HS proteoglycan SYND1 has higher protein and mRNA expression in tumor tissues than non-neoplastic tissues. Such a result was also observed in our group's previous study, which found a significant decrease in CRC tissue's SYND1 protein level than the non-neoplastic colorectal tissue [37]. It is important to note that such studies compared samples from tumor tissues and tissues of patients not affected by neoplasia.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the HPSE gene and protein were already expressed at the colon adenoma stage, which was also observed in the present study [27]. In our previous study, the immunohistochemical analysis revealed a negative correlation between HPSE and HPSE2 proteins in colorectal adenomas [37]. However, the present results clearly showed an increased protein level of both HPSE and HPSE2 in CRC samples compared to adjacent tissues.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, up-regulation of heparanase expression led to down-regulation of syndecan-1, consistent with the results of other studies. 31 , 32 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulfate (HS) proteoglycans are important constituents of the cell membrane, and they act as co-receptors for cellular signaling. cell surface HS proteoglycans are important regulators of cellular migratory, mitogenic, secretory and inflammatory activities (11). Syndecan-1 (SDC1) is a member of the syndecan family, which comprises a transmembrane HS proteoglycan.…”
Section: Introductionmentioning
confidence: 99%